FRI0383 Changes in white matter microstructure correlate with sf-36 mental component subscore in inflammatory npsle. (12th June 2018) - Monahan, R.C.; Beaart- van de Voorde, L.; Magro-Checa, C.; Huizinga, T.; Middelkoop, H.; van Buchem, M.; Ronen, I.; Kaptein, A.; Steup-Beekman, G.
Abstract : Background: The diagnosis and treatment of neuropsychiatric systemic lupus erythematosus (NPSLE) is challenging due to the lack of a diagnostic gold standard and controlled trials. Immunosuppressive therapy is prescribed for immune-mediated NPSLE manifestations, despite little evidence supporting its effectivity. There is increasing evidence for the value of magnetization transfer imaging (MTI) in NPSLE. Recent research has demonstrated that white matter (WM) magnetic transfer ratio histogram peak height (MTR-HPH), a derived-MTI index, is a valuable radiological biomarker for the diagnosis and follow-up in inflammatory NPSLE. 1 It remains unknown whether the changes in WM MTR-HPH also correlate with the change in health-related quality of life (QoL) in these patients. Objectives: To analyse the correlation between change in WM MTR-HPH and change in QoL in different subsets of NPSLE (inflammatory, ischaemic, non-NPSLE). Methods: Patients that visited the Leiden University Medical Centre (LUMC) NPSLE clinic between 2007 and 2015 were included in this study. The attribution process of NP events to SLE and one of its underlying pathogenic mechanisms (ischaemic or inflammatory) was established by multidisciplinary consensus. All patients underwent MRI examination at two different time points and filled in the Short-Form 36 (SF-36). Summary scores were deducted from the SF-36, leading to a Physical Component subscore (PCS) and a Mental Component subscore (MCS) for QoL. Spearman rank correlation coefficient (SR) was used to correlate WM MTR-HPH and the overall difference in change between visits in MCS and PCS. Data was analysed per patient and per event. Results: A total of 15 patients (mean age 39.5±14.1 years, 93% female) were included. Thirty-one NPSLE events were present, of which 68% were inflammatory, 13% ischaemic and 19% non-NPSLE events. Average time between visits was 2.9±1.5 years. The per patient analysis showed statistical significant correlation between WM MTR-HPH and MCS change (SR=0.62; p=0.01) and no effect on PCS change (SR=0.09; p=0.76). The per event analysis showed a significant correlation between change in WM MTR-HPH and MCS in inflammatory events (SR=0.56; p=0.01), but not in ischaemic (p=0.20) or non-NPSLE events (p=0.65). No correlation was observed between change in WM MTR-HPH and PCS in any of the subsets (p=0.21, p=0.40 and p=0.91 respectively). Conclusions: We are the first to demonstrate a correlation between a radiological biomarker and change in the mental component of QoL in inflammatory NPSLE patients. Our study supplies evidence for the use of immunosuppressive therapy in inflammatory NPSLE and supports the use of this radiological biomarker as an outcome measure for future trials in NPSLE. Reference: [1] Magro-Checa C, Ecran E, Wolterbeek R, et al. Changes in White Matter Microstructure Suggest an Inflammatory Origin of Neuropsychiatric Systemic Lupus Erythematosus. Arthritis Rheumatol 2016;68(8):1945–1954. Disclosure of Interest: None declared